1985
DOI: 10.1002/aic.690311117
|View full text |Cite
|
Sign up to set email alerts
|

Form and skin drag contributions to power consumption for the pitched‐blade turbine

Abstract: The determination of power consumption of rotating impellers in an agitated tank has primarily relied on traditional dimensional analysis concepts and correlations. Another traditional approach based on form and skin drag is also possible in determining the power consumption occurring in mixing. This approach, however, appears to have been neglected in the literature on mixing.Traditionally, power number correlations for turbulent flow usually appear as = K pN3D5 where the constant, K, is dependent on the type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Pressure was measured in gassed conditions over the blade. The drag force was calculated as reported by Tay and Tatterson (1985). Sovran et al (1978) reported a drag coefficient of 1.98 for long straight blades placed in unconstricted flow.…”
Section: Effect Of Gas Ventilation On Blade Drag and Cavity Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Pressure was measured in gassed conditions over the blade. The drag force was calculated as reported by Tay and Tatterson (1985). Sovran et al (1978) reported a drag coefficient of 1.98 for long straight blades placed in unconstricted flow.…”
Section: Effect Of Gas Ventilation On Blade Drag and Cavity Pressurementioning
confidence: 99%
“…With negative pressure behind the blade, the sparged gas tries to occupy the entire negative pressure zone. The pres- sure coefficient (C P ) at particular point 'P' was calculated as (Tay and Tatterson, 1985) C P = P P /(0.5 L V 2 F ). Fig.…”
Section: Effect Of Gas Ventilation On Blade Drag and Cavity Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Hockey and Nouri (1996) employed a six-blade 60" PBT and measured mean and rms velocities in the bulk flow and around the turbine using ensemble-averaged and angle-resolved LDA techniques, respectively, and reported a peak velocity of 0.55 Ali et al (1981) observed that only a single trailing vortex was formed at the trailing edge of a four-blade 45" PBT, while Kresta and Wood (1993a) reported that a trailing vortex extending over approximately 20% of the blade was formed at the lower tip of the blade and a smaller one at the top corner of the blade. Tay and Tatterson (1985) reported that the flow over a PBT blade contains boundary layers on the front and back of the blade, a wake behind the blade, and a trailing vortex on the blade tip. However, they indicated that the wake region behind the blade was not significant and the flow resembles a boundary layer.…”
Section: Introduction and Brief Literature Surveymentioning
confidence: 98%
“…The trailing vortices formed behind the blades have a low-pressure core. These low-pressure regions do not contribute to the drag portion of the power consumption of the impeller (Tay and Tatterson, 1985), but may coalesce sparged gas to form gas cavities behind the blades. The trailing vortices have been identified as very important for ligament and sheet production in liquid-liquid dispersion, as shown by Ali et al (1981) and Sheu et a1 (1982), who emphasized that the trailing vortex system is the major flow mechanism responsible for dispersion.…”
Section: Introduction and Brief Literature Surveymentioning
confidence: 99%